Pregabalin use in HIV-infected patients with opioid dependence syndrome - M. Ya. Kissin; N. B. Khalezova; E. A. Gibitova; A. V. Tarnorutskaya; A. N. Ivanov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Te purpose of the current study was to identify an abuse potential of pregabalin in HIVinfected patients with opioid use disorder long time using pregabaline. A cross-sectional study was performed at the St. Petersburg Center for the prevention and control of HIV and infectious diseases. A cohort of 572 HIV-infected patients with opioid use disorder was examined. 96 patients (16,8% of the entire cohort) used pregabalin. 34 of them agreed to participate in the study. Te pregabalin addiction was diagnosed in 23 of 34 observed HIV-infected patients with opioid dependence. People with opioid dependence and presence of organic brain damage of various genesis (toxic exposure, neurological consequences of trauma or infection) are at risk of development of pregabalin dependence. Te use of pregabalin with for self-medication of opiod withdrawal was registered in 11 patients.